The Application of Task Based Instruction of Procedural Activities inTeaching Speaking to Young Learners - Wienny Ardriyati (Dinamika Bahasa dan Budaya, 2015)
This studyappliesthe effectiveness of a model of procedural activities as a media for teaching speaking to young learners.There has been various approaches to the teaching of speaking The technique applied is based on Task Based Instruction.  It means to implement genre teaching in practical terms, and setting out some activities of teaching speaking. The results reveal that there is one student is considered “very good”, he can fulfill the linguistic features and generic structuresin order completely.   Two students are categorized“good”, they can perform the goal, the materials and the steps of the model completely but not in correct order. The rest of the students are categorized “fair”, they can accomplish the tasks but not perfect. This is because they cannot pronounce some words used in the materials and steps of a procedure model correctly.Thus, the findings can be interpreted in a way what is important in procedural activities through demonstration can help students practice speaking very effective and interactive. Key words: demonstration, procedural activities, task based instruction, genre teaching